2009
DOI: 10.1107/s1744309109036665
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structure of human carbonic anhydrase II complexed with acetazolamide reveals insights into inhibitor drug design

Abstract: The crystal structure of human carbonic anhydrase II (CA II) complexed with the inhibitor acetazolamide (AZM) has been determined at 1.1 A resolution and refined to an R(cryst) of 11.2% and an R(free) of 14.7%. As observed in previous CA II-inhibitor complexes, AZM binds directly to the zinc and makes several key interactions with active-site residues. The high-resolution data also showed a glycerol molecule adjacent to the AZM in the active site and two additional AZMs that are adventitiously bound on the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 21 publications
3
111
1
Order By: Relevance
“…2B). The binding and orientation of AZM in CrCAH3 is similar to that in other a-CAs including HCAII (Whittington et al, 2001;Alterio et al, 2009;Sippel et al, 2009). The amide group of the sulfonamide part of the inhibitor is situated approximately 2.0 Å from the zinc atom and positioned in a tetrahedral geometry.…”
Section: The Active Site and Inhibitor Bindingmentioning
confidence: 63%
“…2B). The binding and orientation of AZM in CrCAH3 is similar to that in other a-CAs including HCAII (Whittington et al, 2001;Alterio et al, 2009;Sippel et al, 2009). The amide group of the sulfonamide part of the inhibitor is situated approximately 2.0 Å from the zinc atom and positioned in a tetrahedral geometry.…”
Section: The Active Site and Inhibitor Bindingmentioning
confidence: 63%
“…24,58 The Val121 is present at the mouth of the hydrophobic pocket in the active site of the enzyme, was mutated to Gly, Ala, Ser, Leu, Ile, Lys, and Arg. [59][60][61][62][63][64][65][66][67] It was observed that pnitrophenyl esterase activity and the CO 2 hydrase activity of these CAII variants are directly related to the hydrophobicity of these residues. Therefore, it was recommended that hydrophobic character of such residues is essentially important for catalysis.…”
Section: Three-dimensional Structurementioning
confidence: 97%
“…Therefore, it was recommended that hydrophobic character of such residues is essentially important for catalysis. [59][60][61][62][63][64][65][66][67] The active site of CA is present in the deep, and one side is lined by hydrophobic residues, while hydrophilic residues like Thr199 and Glu106 are resting on the other side. At deep cleft Zn 2+ ion synchronized tetrahedrally with imidazoles of three conserved histidines (His94, His96 and His119) and a water molecule as a fourth solvent ligand 42 .…”
Section: Three-dimensional Structurementioning
confidence: 99%
“…Lamarckian-Genetic Algorithm (LGA) was employed for this study. Human carbonic anhydrase containing native crystal structure of acetazolamide (PDB ID: 3HS4) [62], at resolution of 1.10 Å, which was used throughout the docking study, was being selected using SwissModel [63]. All the water molecules removed from the protein and hydrogens were added.…”
Section: Molecular Dockingmentioning
confidence: 99%